NF‐κB Regulation of LRH‐1 and ABCG5/8 Potentiates Phytosterol Role in the Pathogenesis of Parenteral Nutrition–Associated Cholestasis. Issue 6 (27th August 2021) - Ghosh, Swati; Devereaux, Michael W.; Anderson, Aimee L.; Gehrke, Sarah; Reisz, Julie A.; D'Alessandro, Angelo; Orlicky, David J.; Lovell, Mark; El Kasmi, Karim C.; Shearn, Colin T.; Sokol, Ronald J.
Abstract : Background and Aims: Chronically administered parenteral nutrition (PN) in patients with intestinal failure carries the risk for developing PN‐associated cholestasis (PNAC). We have demonstrated that farnesoid X receptor (FXR) and liver X receptor (LXR), proinflammatory interleukin‐1 beta (IL‐1β), and infused phytosterols are important in murine PNAC pathogenesis. In this study we examined the role of nuclear receptor liver receptor homolog 1 (LRH‐1) and phytosterols in PNAC. Approach and Results: In a C57BL/6 PNAC mouse model (dextran sulfate sodium [DSS] pretreatment followed by 14 days of PN; DSS‐PN), hepatic nuclear receptor subfamily 5, group A, member 2/LRH‐1 mRNA, LRH‐1 protein expression, and binding of LRH‐1 at the Abcg5/8 and Cyp7a1 promoter was reduced. Interleukin‐1 receptor–deficient mice ( Il‐1r −/− / DSS‐PN) were protected from PNAC and had significantly increased hepatic mRNA and protein expression of LRH‐1. NF‐κB activation and binding to the LRH‐1 promoter were increased in DSS‐PN PNAC mice and normalized in Il‐1r −/− / DSS‐PN mice. Knockdown of NF‐κB in IL‐1β–exposed HepG2 cells increased expression of LRH‐1 and ABCG5 . Treatment of HepG2 cells and primary mouse hepatocytes with an LRH‐1 inverse agonist, ML179, significantly reduced mRNA expression of FXR targets ATP binding cassette subfamily C member 2/multidrug resistance associated protein 2 (ABCC2/MRP2), nuclear receptor subfamily 0, groupB, member 2/small heterodimer partner ( NR0B2 /SHP), and ATP binding cassette subfamily B member 11/bile salt export pump ( ABCB11 /BSEP). Co‐incubation with phytosterols further reduced expression of these genes. Similar results were obtained by suppressing the LRH‐1 targets ABCG5/8 by treatment with small interfering RNA, IL‐1β, or LXR antagonist GSK2033. Liquid chromatography–mass spectrometry and chromatin immunoprecipitation experiments in HepG2 cells showed that ATP binding cassette subfamily G member 5/8 ( ABCG5/8 ) suppression by GSK2033 increased the accumulation of phytosterols and reduced binding of FXR to the SHP promoter. Finally, treatment with LRH‐1 agonist, dilauroyl phosphatidylcholine (DLPC) protected DSS‐PN mice from PNAC. Conclusions: This study suggests that NF‐κB regulation of LRH‐1 and downstream genes may affect phytosterol‐mediated antagonism of FXR signaling in the pathogenesis of PNAC. LRH‐1 could be a potential therapeutic target for PNAC.